Topics of Ecology Course in Preparing STEM-based Module - Sulistiyowati, Tutut Indah; Zunaidah, Farida Nurlaila; Mahanal, Susriyati; Zubaidah, Siti; Rahmawati, Ida (KnE Social Sciences, 2024)
Ecology is a compulsory course for students of Bachelors’ Degree in Biology Department. The course lecture includes theories and practices. During the delivery of theories, content conveyed to the students must be in accordance with the course characteristics. Based on interview results, students considered some of the contents to be difficult. The research aims to select topics in Ecology course as a basis for developing STEM (Science, Technique, Engineering, Mathematics)-based module. The expectation is that students could gain a better understanding after the implementation of the STEM-based module approach. The research is qualitative research with a survey method. The data collection were done using survey questionnaire on Google Form platform. The data analysis technique was carried out by elaborating the questionnaire survey results regarding content requirement of the Ecology course. The research finds that several contents delivered in the Ecology course are deemed as difficult. The contents include biogeochemical cycles as well as energy and productivity. Keywords: ecology, course, STEM-based module